Penafsiran Fenomena Flexing Dalam AL-Qur’an: Study Komparatif Tafsir Al-Misbah Dan Tafsir Al-Maraghi - Amir Jihad; Arif Firdausi Nur Romadlon; Edy Wirastho (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze and compare the interpretations of Qur’anic verses related to the phenomenon of flexing, namely ostentatious behavior motivated by the desire to gain praise and recognition from others, as discussed in Tafsir al-Misbah by M. Quraish Shihab and Tafsir al-Maraghi by Ahmad Musthafa al-Maraghi. This research employs a qualitative approach using a library research method. The research data consist of selected Qur’anic verses containing moral values and messages related to ostentation, riya’, ujub, and arrogance, which were selected selectively based on the mapping of relevant verses in Mu‘jam al-Alam wa al-Maudhu‘at fi al-Qur’an al-Karim. Data were collected through documentation techniques by examining primary sources in the form of Tafsir al-Misbah and Tafsir al-Maraghi, as well as secondary sources such as scholarly journals, books, and other academic works. Data analysis was conducted using a comparative (muqāran) tafsir approach by comparing the interpretations of the two exegetes regarding verses related to the theme of flexing. The findings indicate that both exegetes agree in viewing flexing as a reprehensible act that undermines sincerity and diminishes the spiritual value of deeds. However, differences arise in their interpretive emphases: M. Quraish Shihab tends to highlight the social and psychological dimensions, whereas Ahmad Musthafa al-Maraghi emphasizes moral, rational, and linguistic aspects